Edge-to-edge mitral valve repair improves concomitant high-grade tricuspid regurgitation. (3rd October 2022) - Groeger, M; Zeiml, K; Scheffler, J K; Schoesser, F; Schneider, L M; Rottbauer, W; Markovic, S; Kessler, M
Abstract: Background: Mitral regurgitation (MR) and tricuspid regurgitation (TR) often occur simultaneously and symptoms of biventricular heart failure can overlap. There is currently no consensus on the management of combined MR and TR. Purpose: To evaluate the impact of TR on echocardiographic and functional outcome after M-TEER. Methods: 740 patients underwent M-TEER for moderate-to-severe MR at our center from 2010 to 2021. Patients were analyzed according to severity of concomitant TR: low-grade TR (grade ≤ I (trace - mild)), moderate TR (grade II) and high-grade TR (grade III - V (severe - torrential)). After M-TEER, patients were followed up for 12 months and their echocardiographic and functional outcome was evaluated. Results: Low-grade TR was present in 279 patients (37.7%), moderate TR in 170 patients (23.0%) and high-grade TR in 291 patients (39.3%) at the time of M-TEER procedure. Patients with moderate to high-grade TR had higher morbidity resulting in higher EuroSCORE II and STS-Score. At baseline more patients had MR grade ≥III in the high-grade TR group (92.8% vs. 87.1% in the low-grade TR group; p=0.023). Procedural success of M-TEER was achieved similarly in all groups (98.2% vs. 97.6% vs. 95.9%, p=0.22). At discharge 87.6% of patients with low-grade TR and 80.9% of patients with high-grade TR had residual MR grade ≤I (p=0.036). Residual MR grade ≥III was present in 6.0% of low-grade TR patients and 10.5% of high-grade TR patients at discharge (p=0.062). 3 months after M-TEER residual MR ≥III increased to 9.4% vs. 13.4% (p=0.23) and after 12 months further increased to 12.3% vs. 15.3%, respectively (p=0.52). TR grade decreased rapidly and consistently after M-TEER. 3 months after the procedure only 48.0% of high-grade TR patients still had TR grade ≥III (p<0.001). After 12 months this proportion declined to 46.8% (p=0.99). High-grade TR patients had significantly higher mortality (21.5% vs. 18.2% vs. 11.1%, p=0.003) up to 12 months after M-TEER. However, TR-grade ≥III did not independently predict mortality (HR 1.326, 95% CI 0.623–2.824, p=0.46). Conclusion: M-TEER patients with concomitant moderate to high-grade TR had higher morbidity at baseline compared to low-grade TR patients. M-TEER was safe and effective in MR reduction independent of concomitant TR severity. However, high-grade TR patients had an increased risk for mortality after M-TEER, but high-grade TR did not independently predict adverse outcome. After M-TEER TR grade decreased rapidly and significantly in the high-grade TR group. Funding Acknowledgement: Type of funding sources: None.